The study of bread quality enriched with pineapple (ananas comosus) agro waste powder as a novel functional ingredient - Hassan C.Z.; Ramli K.; Suzila I.; Kal-Kausar M.A. (Josip Juraj Strossmayer University of Osijek, Faculty of Food Technology Osijek, 2024)
Indexed by Scopus